Performance Analysis of JL-FinFET with Varied Non-Uniform Doping Concentrations, Fin Height and Fin Width using Device Simulator - M. Hazeem Hariff; Noraini Othman; S. N. Sabki; Alhan Farhanah Abd Rahim (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
With the growth of the MOSFET technology, the size of the transistor becomes smaller which can lead to Short-Channel Effects (SCEs). In order to address the SCEs, multi-gate transistor such as Fin Field-Effect Transistor (FinFET) has been invented. Meanwhile, it is found that the conventional transistor with junctions also has its drawbacks and limitations due to the decrease in the gate length. The SCEs can occur and affect the overall performance of the device with lower switching times and lower current density . In order to address these limitations, new structure of transistor without junction known as a junctionless (JL) transistor has been proposed. In this work, the impact of uniform versus non-uniform doping concentrations, fin height (Hfin) and fin width (Wfin) in JL-FinFET were investigated by using Technology Computer Aided Design (TCAD) Tools. It was found that non-uniform doping concentration of 4 x1018 cm-3 for the source/drain and of 4 x1017 cm-3 for the channel, together with Hfin of 20 nm and Wfin of 4 nm provide the best electrical performance of Ioff = 6.45 x10-17 A, Ion = 6.14 x10-6 A, Ion/Ioff = 9.52 x1010 and DIBL = 11 mV/V. The outcome of this research work can be used as a basis to understand JL-FinFET biosensors for medical applications and more complex JL structures.